The effect of botulinum toxin-A injection into the masseter muscles on prevention of plate fracture and post-operative relapse in patients receiving orthognathic surgery - Sung-Ho Shin; Yei-Jin Kang; Seong-Gon Kim (SpringerOpen, 2018)
Abstract Background Botulinum toxin-A (BTX-A) injection into muscle reduces muscular power and may prevent post-operative complication after orthognathic surgery. The purpose of this study was (1) to evaluate BTX-A injection into the masseter muscle on the prevention of plate fracture and (2) to compare post-operative relapse between the BTX-A injection group and the no injection group. Methods Sixteen patients were included in this study. Eight patients received BTX-A injection bilaterally, and eight patients served as control. All patients received bilateral sagittal split ramus osteotomy for the mandibular setback and additional surgery, such as LeFort I osteotomy or genioplasty. Post-operative plate fracture was recorded. SNB angle, mandibular plane angle, and gonial angle were used for post-operative relapse. Results Total number of fractured plates in patients was 2 out of 16 plates in the BTX-A injection group and that was 8 out of 16 plates in the no treatment group (P = 0.031). However, there were no significant differences in post-operative changes in SNB angle, mandibular plane angle, and gonial angle between groups (P > 0.05). Conclusions BTX-A injection into the masseter muscle could reduce the incidence of plate fracture.